Productivity sorting and mode of export: Marco Grazzi; Chiara Tomasi - Marco Grazzi; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
This paper investigates the relation between firms' productivity and exporting behavior in presence of export intermediaries. Using a cross section of firm-level data for several advanced and developing economies, the study confirms the productivity-sorting prediction according to which domestic firms are less efficient than those resorting to an export intermediary, while the latter are less productive than producers which export directly. Our novel finding is that firms' productivity has a stronger effect on the probability of exporting directly than on the likelihood of exporting indirectly. This suggests for a stronger role of intermediaries in granting foreign market access to a large proportion of small and less productive firms.
Keywords: F14; D22; L22; 330; heterogeneous firms; international trade; direct and indirect exports intermediation